Respiratory presentation of patients infected with enterovirus D68 in Taiwan - Hui-Hsien Pan; Chi-Ren Tsai; Pei-Ju Ting; Fang-Liang Huang; Li-Chung Wang; Chin-Fu Lin; Jiunn-Liang Ko; Ko-Huang Lue; Po-Yen Chen (Elsevier, 2020)
Background: Enterovirus-D68 (EV-D68) has been endemic in Taiwan for some years with a small number of positive cases. Detailed information about respiratory presentation is lacking. This study characterized the clinical course in children admitted to the medical center and regional hospital in Taichung during 2015. Methods: Retrospective chart review of patients with confirmed EV-D68 infection admitted to the medical center and regional hospital in Taichung with respiratory symptoms in the second half of 2015. Past medical history, clinical presentation, management, and course in hospital were collected and analyzed. Simple demographic data and clinical symptoms were also collected from patients confirmed with EV-D68 infection who visited clinics in Taichung. Results: Six children were included. Two patients had a prior history of asthma or recurrent dyspnea, and one had other preexisting medical comorbidities. One child was admitted to the pediatric intensive care unit. All the patients were cured. Cough, rhinorrhea, tachypnea and fever were the most common clinical symptoms among inpatients, while influenza-like illness (ILI) was prevalent in outpatients. Conclusion: EV-D68 infection resulted in respiratory presentations of asthma-like illness in the hospitalized pediatric population. Patients with a prior history of asthma or recurrent dyspnea appear to be more severely affected. Key Words: enterovirus D68, respiratory presentation, taiwan